Ideologies and Mindsets in Tajikistan - E. M. Kozhokin (Сравнительная политика, 2025)
The struggle against Russia unleashed by the West is becoming more widespread. Attempts are also being made to annihilate the co-operative relations that Russia has with the countries of the Eurasian region. In this connection, the study of ideological attitudes and mindsets in the countries of Central Asia, in particular Tajikistan, which has especially close ties with Moscow, is relevant. At the same time, Tajikistan is highly vulnerable to external influence. A particular danger for the republic is posed by the structures of ISIS*, which are actually waging an ideological and psychological war against this secular state. Of all the Central Asian states, Tajikistan has the highest percentage of young people, and it is young people who are most susceptible to radical ideas. The heterogeneity of citizens' mindsets is the focus of the article, and four types of attitudes are identified. The ongoing and relentless struggle for the minds of the citizens of this republic is analysed. Understanding the specificity of the moods of the population of Tajikistan is not only a scientific but also a political imperative. This is due to the fact that the stability and prosperity of this Central Asian country is in Russia's national interests.